EFFECT OF MAKASSAR CULTURE ON THE AGE GROUP TO RESPONSE COMPLIMENT IN ENGLISH - Kamsinah, Kamsinah; Natsir, Nurasia; Aliah, Nuraziza; Fatimah, Ainun (Universitas Islam Sumatera Utara (UISU), 2022)
Exploring the cultural pragmatic speech of the Makassar people of various ages and genders is a popular trend in current pragmatic research. However, most of the previous studies have only obtained data from speakers of different genders and ages and have not addressed the cultural influences that influence them. Therefore, the purpose of this study is to fill in the gaps of previous research by showing that the dominant culture greatly influences verbal actions in response to praise from people living in Makassar, children, adolescents and adults. Three instruments are used in this descriptive research: observations, surveys and interviews with 15 adults, 15 youth and 15 children. The results show that Makassar culture influences the proportion of compliments used by Makassar people. 87% of female responses received praise in adulthood, 13% avoid praise, and 82% of female responses receive praise and 18% avoid praise in adolescence. In adulthood, 60% of their responses are praise, 40% avoid praise, 80% of men respond to praise, 20% reject praise, and 100% of boys accept praise.